Role of canine circovirus in dogs with acute haemorrhagic diarrhoea. (3rd June 2017) - Anderson, A.; Hartmann, K.; Leutenegger, C. M.; Proksch, A. L.; Mueller, R. S.; Unterer, S.
Abstract : Canine circovirus (CanineCV) has been detected in some dogs with severe haemorrhagic diarrhoea, but its pathogenic role is unclear. This study evaluated a suspected association between the presence of CanineCV and acute haemorrhagic diarrhoea syndrome (AHDS) in dogs. The prevalence of CanineCV in dogs with AHDS was compared with that in healthy dogs and those infected with canine parvovirus (CPV). Additionally, time to recovery and mortality rate were compared between CanineCV‐positive and CanineCV‐negative dogs. Faecal samples of dogs with AHDS (n=55), healthy dogs (n=66) and dogs infected with CPV (n=54) were examined by two real‐time TaqMan PCR assays targeting the replicase and capsid genes of CanineCV. CanineCV was detected in faecal samples of two dogs with AHDS, three healthy controls and seven dogs infected with CPV. Among the three groups, there was no significant difference in prevalence of CanineCV. CPV‐infected animals that were coinfected with CanineCV had a significantly higher mortality rate compared with those negative for CanineCV. CanineCV does not appear to be the primary causative agent of AHDS in dogs, but might play a role as a negative co‐factor in disease outcome in dogs with CPV infection.